2022
DOI: 10.1175/bams-d-21-0140.1
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Precipitation on Consecutive Days Occurs More Often in a Warming Climate

Abstract: Extreme precipitation occurring on consecutive days may substantially increase the risk of related impacts, but changes in such events have not been studied at a global scale. Here we use a unique global dataset based on in situ observations and multi-model historical and future simulations to analyse the changes in the frequency of extreme precipitation on consecutive days (EPCD). We further disentangle the relative contributions of variations in precipitation intensity and temporal correlation of extreme pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Analysis of the potential mechanisms leading to the asymmetrical shift of precipitation has identified warming as a major contributor (Goswami et al, 2007;Kong et al, 2020;Sun et al, 2016). To this point, the urban heat island (UHI), the phenomenon of a significant warmer urban areas than the surrounding rural regions, may further affect the asymmetrical variations of rainfall events (Du et al, 2022;Zhu et al, 2019). For example, Yu et al (2022) reported the asymmetrical shift toward less light and more heavy rainfall in the Yangtze River Delta intensified by the rapid urban expansion.…”
mentioning
confidence: 99%
“…Analysis of the potential mechanisms leading to the asymmetrical shift of precipitation has identified warming as a major contributor (Goswami et al, 2007;Kong et al, 2020;Sun et al, 2016). To this point, the urban heat island (UHI), the phenomenon of a significant warmer urban areas than the surrounding rural regions, may further affect the asymmetrical variations of rainfall events (Du et al, 2022;Zhu et al, 2019). For example, Yu et al (2022) reported the asymmetrical shift toward less light and more heavy rainfall in the Yangtze River Delta intensified by the rapid urban expansion.…”
mentioning
confidence: 99%
“…Finally, the relative contribution of precipitation intensity (RC PI ) and temporal clustering of extreme precipitation (RC TC ) to CEP frequency changes were quantitatively calculated as (Du et al ., 2022), RnormalCPI=FPI/FPI+FTC×100, RnormalCTC=FTC/FPI+FTC×100, where |*| represents the absolute value of *. Because F PI or F TC could be negative, we used the absolute value to avoid a relative contribution greater than 100%.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the difference in changes in CEP frequency and changes in adjusted CEP frequency (the change in CEP frequency minus the changes in adjusted CEP frequency between both periods) would then indicate the effect related to F PI . Finally, the relative contribution of precipitation intensity (RC PI ) and temporal clustering of extreme precipitation (RC TC ) to CEP frequency changes were quantitatively calculated as (Du et al, 2022),…”
Section: Relative Contribution Of Driving Factors To Cep Frequency Ch...mentioning
confidence: 99%
See 1 more Smart Citation
“…From the time perspective, large values of 𝑅(𝑡) indicate the most stationary periods. A minimum threshold is often defined to separate stationary from non-stationary periods: for instance, 2 days for weather regimes (De Luca et al, 2019;Francis et al, 2020) and extreme precipitation (Du et al, 2022), 5-6 days for warm spells (Berkovic and Raveh-Rubin, 2022;Rousi et al, 2022b), 5-25 days for geopotential anomalies (Dole and Gordon, 1983), or 2 seasons for droughts (Ford and Labosier, 2014). In the phase space, the stationarity of any state x 0 can be described from the distribution of its residence times 𝑅 x 0 ∼ P {𝑅(𝑡) s.t.…”
Section: Residence Timesmentioning
confidence: 99%